Big and bright : deep in the heart of Texas high school football - Levy, Gray, 1968- (Taylor Trade Publishing, 2015)
For many cities of Texas, high school football is more than a sport-it's the glue of their community. Author Gray Levy, disillusioned with the state of the education system, traveled to Texas to see what they were doing right. What he found will both confirm and debunk common presumptions about high school football in Texas.